The Bicultural I: A Social and Cognitive Approach for Understanding the Psychology of Acculturation - Sapiro, Michael (Journal of International Students, 2011)
This paper investigates the processes and challenges of creating a socially integrated, empowered immigrant identity by exploring the concepts acculturation model. The author examines the psychology of acculturation and the processes for creating a socially integrated bicultural self for immigrants who retain cultural traditions while adapting to new social norms and practices. The complexity of this process embraces principles from both social and cultural psychological paradigms and emphasizes a non-dual approach for creating meaning for a bicultural individual acculturating into a new society.